Психолого-педагогічні аспекти творчого розвитку дошкільників у процесі музичної діяльності - Медвідь Тетяна; Гнатів Зоряна; Човрій Софія; Medvid Tetiana; Hnativ Zoriana; Sofiya Chovriy; Csoóri Zsófia (Видавнича група «Наукові перспективи», 2026)
Резюме. У статті розглядаються психолого-педагогічні аспекти творчого розвитку дітей дошкільного віку засобами музичного мистецтва в контексті сучасних освітніх трансформацій. Актуальність дослідження зумовлена необхідністю пошуку дієвих механізмів формування креативної особистості, здатної до нестандартного мислення та емоційно-ціннісного сприйняття навколишнього світу. У дослідженні проаналізовано музичну діяльність як багатогранний інструмент впливу на когнітивну та емоційну сфери дитини, акцентуючи увагу на важливості гуманізації освітнього процесу. Особливу увагу в роботі приділено віковій періодизації дошкілля – від раннього до старшого дошкільного віку. Висвітлено специфіку музичного розвитку на кожному етапі: від первинних сенсорних відчуттів та наслідування у ранньому віці до формування стійких естетичних суджень, усвідомленої художньої сприйнятливості та здатності до імпровізації у старших дошкільників. У статті розкрито роль різних видів музичної діяльності, зокрема співу, слухання музики, музично-ритмічних рухів та гри на дитячих інструментах у стимулюванні творчої активності вихованців. Окремий акцент зроблено на важливості ігрових методів навчання, що виступають природним середовищем для реалізації дитячих фантазій та утвердження індивідуальності. У висновках підкреслюється, що ефективність музично-естетичного виховання залежить від створення сприятливого творчого середовища та партнерської взаємодії педагога з дитиною. Стаття доводить, що систематичне залучення дошкільників до музичної творчості забезпечує формування цілісної естетичної картини світу та закладає фундамент для успішної самореалізації особистості в майбутньому. Матеріал статті має практичне значення для музичних керівників, вихователів закладів дошкільної освіти та студентів музично-педагогічних спеціальностей.

Abstract. The article comprehensively examines the psychological and pedagogical aspects of the creative development of preschool children through the medium of musical art within the context of modern educational transformations and social challenges. The relevance of the research is determined by the urgent necessity to find effective mechanisms for shaping a creative personality capable of divergent thinking, innovative approaches, and an emotional-value perception of the surrounding world. The study analyzes musical activity as a multifaceted instrument of profound influence on a child’s cognitive, social, and emotional spheres, emphasizing the critical importance of humanizing the educational process in modern preschool institutions. Particular attention is paid to the systematic age periodization of preschool years, from early childhood to senior preschool age. The specific characteristics of musical development at each individual stage are highlighted: from primary sensory perceptions and basic imitation in early childhood to the formation of stable aesthetic judgments, conscious artistic susceptibility, and the advanced capacity for independent improvisation in senior preschoolers. The article reveals the fundamental role of various types of musical activities, including singing, music appreciation, musical-rhythmic movements, and collective playing on children’s instruments, in stimulating the creative activity of pupils. A special emphasis is placed on the importance of game-based learning methods, which serve as a natural and supportive environment for the realization of children’s fantasies and the assertion of their unique individuality. The conclusions emphasize that the overall effectiveness of musical-aesthetic education depends on the creation of a favorable creative environment and the partnership-based interaction between the educator and the child. The article proves that the systematic involvement of preschoolers in musical creativity ensures the formation of a holistic aesthetic worldview and lays a solid foundation for successful personal self-realization in the future. The material of the article is of significant practical value for music directors, educators of preschool education institutions, and students of music-pedagogical specialties.
Psychological and pedagogical aspects of creative development of preschoolers in the process of musical activity
Весь випуск: https://perspectives.pp.ua/index.php/nauka/issue/view/440
Keywords: креативність; музична діяльність; психоемоційний розвиток; дошкільний вік; вікова періодизація; музично-естетичне виховання; creativity; musical activity; psycho-emotional development; preschool age; age periodization; musical-aesthetic education